Use of Alfentanil in Palliative Care - José António Ferraz Gonçalves; Filipa Sousa; Lucy Alves; Patrícia Liu; Sara Coelho (MDPI AG, 2020)
Alfentanil is used for chronic pain relief in palliative care. However, there is a dearth of data on its use. For this reason, a decision was made to review the use of alfentanil in palliative care. Retrospective study was carried out in a palliative care service. The files of patients who received alfentanil as an intravenous or subcutaneous continuous infusion for pain relief, between January 2018 and April 2019. In total, 111 patients received alfentanil out of 113 admissions. Of them, 56 were male, and the median age was 70 years. The median number of days on alfentanil was 6 (range 1 to 129). The most frequent primary reasons for switching to alfentanil was uncontrolled pain in 52 (46%) patients and renal impairment in 24 (21%) patients. The median 24-h initial dose of alfentanil was 4 mg (1-20), and the median final 24-h dose of alfentanil was 5 mg (1-60), (p < 0.001). The initial 24-h median number of rescue doses was 2 (0-8), and the final median number of rescue doses was 1 (0 to 8), (p = 0.025). In 56 patients who were on alfentanil for at least 7 days, the dose decreased in 3 (5%), remained stable in 10 (18%) and increased in 43 (77%). The patient on alfentanil for 129 days maintained the same dose throughout that period. Alfentanil can be a useful second-line opioid. The induction of tolerance does not seem to be particularly rapid with alfentanil.